Dimensi Konsep Diri Aktivis Perempuan Penyintas Cybermisogyny Di Instagram - Annisa Muasrani; Welly Wirman; Ringgo Eldapi Yozani (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the self-concept of cybermisogyny survivors among female activists of the HMI-Wati Corps (KOHATI) in Pekanbaru, focusing on the dimensions of self-image, ideal self, and self-esteem. This study used a qualitative approach with a participatory and phenomenological Community-Based Research (CBR) method. Data were collected through in-depth interviews with six informants selected using snowball sampling. The results show that cybermisogyny causes a shift in self-image from positive to negative through the internalization of external assessments such as body shaming and objectification. In the ideal self dimension, there is a shift from an orientation towards freedom of expression to a more defensive orientation, emphasizing mental resilience and self-protection. Meanwhile, self-esteem decreases due to social pressure, but can be recovered through social support, emotional validation, and involvement in a supportive organizational environment. This study confirms that cybermisogyny not only impacts digital communication but also women's psychological structure, as well as the importance of social support and safe spaces in the process of women's recovery and empowerment in the digital space